Website content accessibility of 30,000 cypriot web sites - Zaphiris, Panayiotis; Zacharia, Giorgos (My University, 2001)
This paper extends previous studies [10, 12, 13] that investigated the accessibility of different web sites of specific content and context to an analysis of the whole web of a specific country (Cyprus). To our knowledge no previous study has analyzed such a big number of web sites for accessibility in a single study. More specifically this paper evaluates the compliance of 30,000 Cyprus related websites spidered by Arachne (http://search.kypros.org ) search engine. The 30,000 Cyprus related websites where evaluated for accessibility using the Bobby (http://www.cast.org/bobby/) accessibility tool. Statistical analysis and comparison of the accessibility ratings for the different main domain categories (commercial, academic, governmental, and organizational) of the Cypriot web are also provided.